Modelling of Urban Forest Management System for DBKL - Mohd Zaki, Shahabuddin (2011)
The necessity for urban forest management system among local authorities is important as it will change the efficiency of street trees planning and management. This research work addressed the main objective to develop a prototype system for urban forest management with case study implementation for Dewan Bandaraya Kuala Lumpur (DBKL). The specific objectives are to derive design requirements to implement tree inventory, tree works maintenance program and trees emergency incidents response. The methodology of system development is applied from Nunamaker’s System Development Research Method. The outcome of study is the prototype of Urban Forest Management system with expectation to improve urban trees management effectiveness and efficiency. The system covers modules in inventorying tree details, managing trees work maintenance program, and handling public requests and complaints of failure urban trees incidents.